A multiaxial electrical switching in a one-dimensional organic–inorganic (pyrrolidinium)2Cd2I6 ferroelectric and photoluminescent crystal. Issue 24 (4th June 2021) - Rok, Magdalena; Zarychta, Bartosz; Bil, Andrzej; Trojan-Piegza, Joanna; Medycki, Wojciech; Miniewicz, Andrzej; Piecha-Bisiorek, Anna; Ciżman, Agnieszka; Jakubas, Ryszard
Abstract : A novel photoluminescent–ferroelectric crystal of (C4 H10 N)2 [Cd2 I6 ] (PCdI ) has been obtained and characterized. Abstract : Ferroelectric materials exhibiting more than one polar phase are very attractive in terms of application. The advantage of such materials is temperature-dependent switching between two different ferroelectric states. Here we report on the discovery of a unique, continuous ferroelectric – ferroelectric transformation in (C4 H10 N)2 [Cd2 I6 ], PCdI at 220 K. Thermal measurements suggest that phase transition is close to the continuous one. Both phases belong to the same polar monoclinic Cc space group. Temperature-variable X-ray diffraction measurements of single crystals confirm the polar nature of the two phases (I and II). The anionic network is in the form of [Cd2 I6 ] 2− 1D chains, with pyrrolidinium cations planted between them. To our knowledge, there are few examples of a structure with chains formed by tetrahedral units. Electrical and dielectric properties were measured for the samples in crystalline and thin-layer film forms. The ferroelectric properties of phases I and II were confirmed by the reversible pyroelectric effect as well as by the polarisation–electric field (P–E) loop tests, and these results were supported by DFT calculations. Strong nonlinear optical properties (NLO) were confirmed by SHG measurements. Additionally, the photoluminescent properties were investigated with the temperature dependence of the spectra of both photoluminescence excitation (PLE) and emission (PL). The broadband luminescence revealed to be thermally quenched from cryogenic temperatures to room temperature.